Childhood vitiligo: Clinical epidemiological profile - Asmae Lahlou; Hanane Baybay; Salim Gallouj; Fatima-Zohra Mernissi (Our Dermatology Online, 2017)
Objective: To study the clinical and the epidemiologic profiles of childhood vitiligo. Patients and Methods: We prospectively analyzed the clinical data of children with vitiligo presented to the dermatology derpartement at University Hospital - Fès for 5 years from May 2011 to May 2016. This study included 31 patients. All patients were assessed for the natural history, clinical characteristics, family history, and associated abnormalities of vitiligo. Results: Of the 31 children with vitiligo 9 (29,03%) were boys and 21 (67.74%) were girls. The mean age of onset of the vitiligo was 10 years. The mean duration of the disease was 38,9 weeks. The most common type of vitiligo was vitiligo vulgaris (49.5%) followed by focal vitiligo (39%), acrofacial vitiligo (32%), and segmental vitiligo (16%) The most frequent site of onset was the extremities followed by the head and the neck, then the trunk and the genitalia. Of the 31 children with vitiligo, 39% had a family history and 4 % had an antecedent of autoimmune diesease like le diabète, une thyroïdite, l'anémie et le psoriasis, retrouvé. Conclusion: Our children have a strong family history of vitiligo and they are developing the disease at a slightly older age compared with those of other studies; however, other epidemiologic features appear to be similar to those reported in the previously published studies.